Analisis Strategi Penetapan Harga yang Dilakukan Salah Satu Distributor Hannochs di Tembung dalam Menghadapi Persaingan - Arsyrah Fitri; Riski Lainatus Sifa; Teresia Bunga; Aurora Elise Putriku; Lenti Susanna Saragih (Pusat Riset dan Inovasi Nasional, 2024)
Price is very important in marketing strategy because it interacts with all other aspects to determine the overall effectiveness of the strategy. Pricing objectives should be aligned with overall marketing objectives. The aim of this research is to find out the pricing strategy used by one of the Hannochs distributors in Tembung in facing competition between other distributors. The research method used in this research is descriptive qualitative. The technique used to obtain data in this research was an interview with one of the Hannochs distributors and also using literature study techniques. Based on the results of interviews, Hannochs distributors in Temhung face competition by setting prices based on comparisons with other stores, providing bonuses, and using discount strategies to attract customers. They also make price changes to maintain consumer appeal even though the profits taken are lower. This strategy is successful in increasing customer loyalty because prices are cheaper than competitors.